Epithermal precious metal deposits physicochemical constraints, classification characteristics and exploration guidelines - McIver, Donald A (Rhodes University, Faculty of Science, Department of Geology, 1997)
Epithermal deposits include a broad range of precious metal, base metal, mercury, and stibnite deposits. These deposits exhibit a low temperature of formation (180-280Â°C) at pressures of less than a few hundred bars (equivalent to depths of 1.5 - 2.0lkm). Epithermal gold deposits are the product of large-scale hydrothermal systems which mostly occur in convergent plate margin settings. Associated volcanism is largely of andesitic arc (calcalkaline to alkaline), or rhyolitic back-arc type. Porphyry Cu-Mo-Au deposits form deeper in the same systems. Genetic processes within individual deposits take place in an extremely complex manner. The resultant mineral associations, alteration styles and metal deposition patterns are even more complicated. Many attempts have been made to classify epithermal deposits based on mineralogy and alteration, host rocks, deposit form, genetic models, and standard deposits. For the explorationist, the most useful classification schemes should be brief, simple, descriptive, observationally based, and informative. Ultimately, two distinct styles of epithermal gold deposits are readily recognised: high-sulphidation, acid sulphate and low-sulphidation, adularia-sericite types. The terms high-sulphidation (HS) and low-sulphidation (IS) are based on the sulphidation state of associated sulphide minerals, which, along with characteristic hydrothermal alteration, reflect fundamental chemical differences in the epithermal environment. Highsulphidation-type deposits form in the root zones of volcanic domes from acid waters that contain residual magmatic volatiles. The low-sulphidation-type deposits form in geothermal systems where surficial waters mix with deeper, heated saline waters in a lateral flow regime, where neutral to weakly acidic, alkali chloride waters are dominant. The HSILS classification, combined with a simple description of the form of the deposit, conveys a large amount of information on mineralogy, alteration, and spatial characteristics of the mineralisation, and allows inferences to be drawn regarding likely regional controls, and the characteristics of the ore-forming fluids. The modern understanding of these environments allows us to quite effectively identify the most probable foci of mineral deposition in any given district. Current knowledge of these deposits has been derived from studies of active geothermal systems. Through comparison with alteration zones within these systems, the exploration geologist may determine the potential distribution and types of ore in a fossil geothermal system. Alteration zoning specifically can be used as a guide towards the most prospective part of the system. Epithermal gold deposits of both HS- and LS-styles are nevertheless profoundly difficult exploration targets. Successful exploration must rely on the integration of a variety of exploration techniques, guided by an understanding of the characteristics of the deposits and the processes that form them. There are no simple formulae for success in epithermal exploration: what works best must be determined for each terrain and each prospect. On a regional scale tectonic, igneous and structural settings can be used, together with assessment of the depth of erosion, to select areas for project area scale exploration. Integrated geological-geophysical interpretation derived from airborne geophysics providesa basis of targeting potential ore environments for follow-up. Geology, geochemistry and surface geophysics localise mineral concentrations within these target areas
Keywords: Precious metals; Geothermal resources